The Potential of Arbuscular Mycorrhizal Fungi (AMF) as Biocontrol Agent Against Stem Rot Diseases Caused Sclerotium rolfsii of peanut (Arachis hypogaea L) - Fradilla Swandi; Eri Sulyanti; Darnetty Darnetty; Reflin Reflin (Department of Crop Science, Faculty of Agriculture, Andalas University, 2020)
This study was conducted to assess the biocontrol efficacy of arbuscular mycorrhizae fungi (AM Fungi) against stem rot disease caused by Sclerotium rolfsii Sacc. in peanut. The AM Fungi can be associated with almost all types of plants. The purpose of this study was to obtain isolates of arbuscular mycorrhiza fungi (AMF) as a potential biofungisida against Sclerotium rolfsii and can characterize the mechanism of the FMA in controlling S.rolfsii (salicylic acid) on peanut plants. The AM Fungi inoculant (40 spores g-1 in concentration) was introduced to peanut seedling (25 g plant-1 ) at planting time where as Sclerotium rolfsii inoculated 30 days after planting time. The experiment was arranged in the completely randomized design (CRD), which is 7 treatment sand repeated 10 times in the greenhouse experiment. The data were analyzed using analysis of variance (ANOVA) using STAT program 8 and the Tukey test at 5% significance level. The AM Fungi treatments showed significantly redused the percentage of disease severity in infected peanut plants around 34.28% - 57.15% and longer incubation period, respectively. They increased root colonization (20,00 - 46.67%) with a middle to high category. The AM Fungi C isolate (isolated from Solok county), and the A isolate (isolated from Payakumbuh city) were the best as a biocontrol against S rolfsii (57.15%), followed by isolate D (isolated from Padang Pariaman county) 54,30 %. They also increased Salicylic acid content 1,4 times (70.72 ppm) compared to control (49,59 ppm). It can be concluded that the application of AM Fungi as a biocontrol agent played an important role in plant resistance and exhibit greater potential to protect peanut plants against S. rolfsii.